2019
DOI: 10.2460/ajvr.80.2.168
|View full text |Cite
|
Sign up to set email alerts
|

Effect of contrast medium injection rate on computed tomography-derived renal perfusion estimates obtained with the maximum slope method in healthy Beagles

Abstract: OBJECTIVE To evaluate the effect of contrast medium injection rate on CT-derived renal perfusion estimates obtained with the maximum slope method in healthy small dogs. ANIMALS 6 healthy sexually intact male purpose-bred Beagles. PROCEDURES All dogs underwent CT perfusion analysis 3 times in a crossover design, receiving a different contrast medium injection rate (1.5, 3.0, and 4.5 mL/s) each time, with a 1-week interval between imaging sessions. All CT images were obtained at the level of the left renal hilus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…First, the CT perfusion for RBF was performed under general anesthesia after placing the ultrasonic flow probe, and the study design was not consistent with the clinical condition. The long duration of anesthesia could affect the CT-derived renal blood volume; however, the CT perfusion RBF values were similar to those measured immediately after inducing anesthesia using the same techniques in our previous study (17). Second, this study only included a relatively small number of dogs (n = 5) because the procedure used to measure direct RBF was invasive.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…First, the CT perfusion for RBF was performed under general anesthesia after placing the ultrasonic flow probe, and the study design was not consistent with the clinical condition. The long duration of anesthesia could affect the CT-derived renal blood volume; however, the CT perfusion RBF values were similar to those measured immediately after inducing anesthesia using the same techniques in our previous study (17). Second, this study only included a relatively small number of dogs (n = 5) because the procedure used to measure direct RBF was invasive.…”
Section: Discussionmentioning
confidence: 77%
“…To the best of our knowledge, renal CT perfusion using the maximum slope method in dogs was evaluated in only our previous study on the effect of the contrast medium injection rate on CT perfusion (17). However, the correlation between CT perfusion analysis and true renal perfusion in dogs remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…One study demonstrated that rapid administration of contrast medium is required for the quantitative analysis of hepatic PCT. 17 Conversely, another study reported that even a low contrast medium injection rate of 1.5 mL/second is sufficient for the evaluation of renal perfusion. 16 The current study found that the contrast medium injection rate affected brain PCT when a 24-gauge was used.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies 16,17 in veterinary medicine have also analyzed the effects of variables related to contrast medium injection on PCT; however, the results have varied. One study demonstrated that rapid administration of contrast medium is required for the quantitative analysis of hepatic PCT.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation